Clinical usefulness of the second peak of radial systolic blood pressure for estimation of aortic systolic blood pressure - Kohara, K; Tabara, Y; Tomita, H; Nagai, T; Igase, M; Miki, T (Journal of human hypertension, 2009)
Central aortic blood pressure (BP), obtained from radial arterial waveform using the transfer function method (TFM), has been shown to have prognostic value independently of brachial BP. In this study, the relationship between peripheral systolic BP (SBP) and aortic SBP was evaluated. We further investigated whether TFM-derived aortic SBP can be estimated by information obtained from the radial waveform. The radial waveform was analysed to obtain the first peak of radial SBP (SBP1), second peak of radial SBP (SBP2), radial augmentation index (AI) (radial (SBP2−DBP)/(SBP1−DBP) × 100 and aortic SBP and AI using TFM in 233 subjects in the supine position. Measurements were repeated after changing position to the prone position. The constructed equation was validated in 149 community residents with different backgrounds. Radial SBP2 was closer to TFM-derived aortic SBP compared with brachial SBP. TFM-derived aortic SBP was approximated by the equation: aortic SBP=18.9—radial SBP2−0.03 × HR—0.214 × radial AI ( r 2 =0.992). The equation was also applicable to predicting aortic SBP in the prone position as well as in different populations (mean difference between predicted aortic SBP and TFM-derived aortic SBP: −0.01±1.34 and 1.05±1.47 mm Hg, respectively). Radial arterial waveform analysis can be used for estimation of TFM-derived aortic SBP.